Resin composition, prepreg, resin film, metal-clad laminate, printed wiring board, and semiconductor package

The resin composition, incorporating a vinylbenzyl compound and a high-melting-point phosphorus compound, addresses the need for high heat resistance and low transmission loss in electronic device substrates, enhancing performance in high-frequency applications.

JP2025018158APending Publication Date: 2025-02-06RESONAC CORP

Patent Information

Application Number
JP2023121640
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

Existing substrate materials for electronic devices face challenges in achieving low transmission loss and high heat resistance, particularly in high-frequency applications.

Method used

A resin composition comprising a vinylbenzyl compound and a phosphorus compound with a melting point of 230°C or higher, optionally with an inorganic filler and a silicone condensate, is used to create prepregs, resin films, metal-clad laminates, printed wiring boards, and semiconductor packages, enhancing heat resistance and dielectric properties.

Benefits of technology

The resin composition provides products with improved heat resistance and dielectric properties, suitable for high-frequency applications, while maintaining low transmission loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018158000001
    Figure 2025018158000001
  • Figure 2025018158000002
    Figure 2025018158000002
  • Figure 2025018158000003
    Figure 2025018158000003
Patent Text Reader

Abstract

To provide a resin composition that yields a product with high heat resistance, and also provide a prepreg, a resin film, a metal-clad laminate, a printed wiring board, and a semiconductor package, produced using the resin composition.SOLUTION: A resin composition comprises a compound with a vinylbenzyl group, and a phosphorous compound with a melting point of 230°C or higher.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a resin composition, a prepreg, a resin film, a metal-clad laminate, a printed wiring board, and a semiconductor package. [Background technology]

[0002] With the increasing demand for high-speed processing of huge amounts of data, substrate materials with low transmission loss in the high-frequency range are required for electronic devices such as portable communication devices such as smartphones, personal computers, industrial computers, servers, large servers, routers, and mobile base stations. In addition, substrate materials for electronic devices, etc. are also required to have heat resistance to withstand the operating environment.

[0003] Patent Document 1 describes a thermosetting resin composition containing a vinylbenzyl compound as a resin composition having dielectric properties suitable for high frequency band applications. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-119531 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present disclosure is to provide a resin composition capable of providing products having excellent heat resistance, and a prepreg, a resin film, a metal-clad laminate, a printed wiring board, and a semiconductor package using the resin composition. [Means for solving the problem]

[0006] Examples of embodiments are listed below. The present invention is not limited to the following embodiments. <1> A resin composition comprising a compound having a vinylbenzyl group and a phosphorus-based compound having a melting point of 230°C or higher. <2> Further comprising an inorganic filler, <1> The resin composition according to claim 1. <3> Further comprising a silicone condensate having an alkoxy group and a phenyl group. <1> or <2> The resin composition according to claim 1. <4> <1> ~ <3> A prepreg comprising the resin composition according to any one of claims 1 to 5 or a semi-cured product of the resin composition. <5> <1> ~ <3> 13. A resin film comprising the resin composition according to claim 12 or a semi-cured product of the resin composition. <6> <1> ~ <3> 13. A metal-clad laminate comprising a cured product of the resin composition according to claim 12 and a metal foil. <7> <1> ~ <3> A printed wiring board comprising a cured product of the resin composition according to any one of claims 1 to 5. <8> <7> A semiconductor package comprising the printed wiring board according to claim 1 and a semiconductor element. Effect of the Invention

[0007] The present disclosure makes it possible to provide a resin composition capable of providing products with excellent heat resistance, as well as a prepreg, a resin film, a metal-clad laminate, a printed wiring board, and a semiconductor package that use the resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.

[0009] In the present disclosure, a numerical range indicated using "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in the present disclosure, the upper limit or lower limit of a certain numerical range may be replaced with the upper limit or lower limit of another numerical range. In addition, the upper limit or lower limit of a numerical range described in the present disclosure may be replaced with a value shown in the examples.

[0010] In the present disclosure, unless otherwise specified, each component may contain one or more corresponding substances. In the present disclosure, when a plurality of substances corresponding to each component are present in the resin composition, the content of each component in the resin composition means the total amount of the plurality of substances present in the resin composition, unless otherwise specified.

[0011] In this disclosure, unless otherwise specified, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are values ​​measured by the following procedure.

[0012] The weight average molecular weight and number average molecular weight are calculated from a calibration curve using standard polystyrene by gel permeation chromatography (GPC). The calibration curve is approximated by a third order equation using standard polystyrene: TSKstandard POLYSTYRENE (Type: A-2500, A-5000, F-20, F-80) (manufactured by Tosoh Corporation, trade name). The GPC conditions are as follows.

[0013] Equipment: High-speed GPC equipment "HLC-8320GPC" (Tosoh Corporation, product name) Detector: Ultraviolet absorption detector "UV-8320" (Tosoh Corporation, product name) Columns: Guard column; TSKgel guardcolumn Super(HZ)-M+, column; TSKgel SuperMultipore HZ-M (2 columns), reference column; TSKgel SuperH-RC (2 columns) (all products of Tosoh Corporation) Column size: 4.6 x 20 mm (guard column), 4.6 x 150 mm (column), 6.0 x 150 mm (reference column) Eluent: Tetrahydrofuran Sample concentration: 10mg / 1mL Injection volume: 20μL or 2μL Flow rate: 0.35mL / min Measurement temperature: 40℃

[0014] [Resin composition] A resin composition according to an embodiment of the present disclosure includes a compound having a vinylbenzyl group and a phosphorus-based compound having a melting point of 230° C. or higher.

[0015] <Compounds having a vinylbenzyl group> A compound having a vinylbenzyl group (hereinafter, sometimes referred to as a "vinylbenzyl compound") can have one or more vinylbenzyl groups, and may have two or more vinylbenzyl groups. By having one or more vinylbenzyl groups in one molecule, the vinylbenzyl compound can obtain a cured product by promoting the reaction of the vinylbenzyl group within a molecule or between molecules using heating or the like.

[0016] The vinylbenzyl compound may be any one of a monomer, an oligomer, and a prepolymer, and a combination of two or more of these may be contained in the resin composition.

[0017] When the vinylbenzyl compound is a monomer, one or more vinylbenzyl groups may be introduced into the base compound. The oligomer may be a compound with a low degree of polymerization in which two or more of this monomer are polymerized. The prepolymer may be a compound in which one or more vinylbenzyl groups are introduced into the resin skeleton, and may be a monomer, oligomer, or a polymer of a combination thereof having one or more vinylbenzyl groups. Both the oligomer and the prepolymer preferably contain a certain amount of unreacted vinylbenzyl groups, and are in a state in which a curing reaction is initiated by heating or the like.

[0018] In the monomer of the vinylbenzyl compound, the number of vinylbenzyl groups may be 1 or more or 2 or more, for example, 2 to 4 or 2 to 3.

[0019] In the oligomer or prepolymer of the vinylbenzyl compound, the number of vinylbenzyl groups in the molecule may be 1 or more, but it is preferable that the monomer constituent unit contains 1 or 2 or more vinylbenzyl groups, and the monomer constituent unit may contain 2 to 4 or 2 to 3 vinylbenzyl groups.

[0020] In the vinylbenzyl compound, the vinylbenzyl group may be any of o-vinylbenzyl group, m-vinylbenzyl group and p-vinylbenzyl group. When two or more vinylbenzyl groups are contained in one molecule of the vinylbenzyl compound, the two or more vinylbenzyl groups may be the same or different isomers. From the viewpoint of dielectric properties, it is preferable that at least one p-vinylbenzyl group is contained in one molecule of the vinylbenzyl compound.

[0021] In one molecule of the vinylbenzyl compound, the content of p-vinylbenzyl groups may be 10 to 100 mass %, 20 to 80 mass %, 30 to 70 mass %, or 40 to 60 mass % relative to the total mass of all vinylbenzyl groups.

[0022] In the vinylbenzyl compound, the vinylbenzyl group may be unsubstituted or may have a substituent. When the vinylbenzyl compound has a substituent, the substituent may be, for example, an aliphatic hydrocarbon group having 1 to 20, 1 to 8, or 1 to 4 carbon atoms, or may be an alkyl group having these carbon numbers. The vinylbenzyl group may have a halogen atom as a substituent, for example, a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom. In the vinylbenzyl group, at least one of the 1 to 4 hydrogen atoms bonded to the benzene ring may be substituted, and when the vinylbenzyl group has two or more substituents, the substituents may be the same or different from each other. When the vinylbenzyl compound has two or more vinylbenzyl groups, the presence or absence, number, and type of the substituents between the two or more vinylbenzyl groups may be the same or different from each other. From the viewpoint of dielectric properties, the vinylbenzyl compound preferably has at least one unsubstituted vinylbenzyl group, and all the vinylbenzyl groups may be unsubstituted.

[0023] The vinylbenzyl compound is preferably a hydrocarbon compound, and the structure other than the vinylbenzyl group may be any of a non-aromatic hydrocarbon structure such as a chain hydrocarbon structure or an alicyclic hydrocarbon structure, and an aromatic hydrocarbon structure, but is preferably an aromatic hydrocarbon structure. The aromatic hydrocarbon structure may be a monocyclic or polycyclic aromatic ring, a condensed ring of two or more aromatic rings, a condensed ring of an aromatic ring and a non-aromatic ring, etc.

[0024] Examples of the aromatic hydrocarbon structure include an indene ring, an indane ring, a phenanthrene ring, an acenaphthylene ring, and a fluorene ring. More preferably, the vinylbenzyl compound is a compound having an indene ring. It is also preferable that the vinylbenzyl group is directly bonded to a carbon atom on the ring of the aromatic hydrocarbon structure. When the vinylbenzyl compound contains an aromatic hydrocarbon structure, the indene ring, indane ring, phenanthrene ring, acenaphthylene ring, fluorene ring, etc. may be unsubstituted or may have a substituent, except for the bonding site with the vinylbenzyl group. Examples of the substituent include those described above for the vinylbenzyl group. For example, when the vinylbenzyl compound contains an indene ring, at least one of the multiple hydrogen atoms bonded to the indene ring may be substituted, and when there are two or more substituents, they may be the same or different from each other. When the vinylbenzyl compound contains an aromatic hydrocarbon structure, from the viewpoint of dielectric properties, the indene ring, indane ring, phenanthrene ring, acenaphthylene ring, fluorene ring, etc. may be unsubstituted except for the bonding site with the vinylbenzyl group.

[0025] The monomers of the vinylbenzyl compounds will be described below. The vinylbenzyl compound as a monomer is preferably a hydrocarbon compound, and among the hydrocarbon compounds, it is preferably a compound having an indene ring, an indane ring, a phenanthrene ring, an acenaphthylene ring, a fluorene ring, or the like, or a combination thereof, more preferably a compound having an indene ring, a fluorene ring, or a combination thereof, and even more preferably a compound having an indene ring.For example, the vinylbenzyl compound may be a monomer having one or more vinylbenzyl groups and one indene ring in one molecule.

[0026] One example of a vinylbenzyl compound is a monomer having an indene ring and one or more vinylbenzyl groups bonded to any one of the 1-, 2-, and 3-positions of the indene ring.

[0027] Specific examples of the vinylbenzyl compound include a monomer represented by the following formula (1).

[0028] [ka]

[0029] In formula (1), n ​​is 1, 2 or 3, but may be 2 or 3. The mixture of monomers represented by formula (1) may contain a plurality of monomers having different n's. In this case, n is preferably 2 to 3 on average, and more preferably 2.0 to 2.5.

[0030] In formula (1), the vinylbenzyl group may be directly bonded to any of the carbon atoms at the 1st, 2nd, and 3rd positions of the indene ring, but is preferably bonded to the 1st position or a combination of the 1st and 3rd positions. One or two vinylbenzyl groups may be bonded to each position. For example, the vinylbenzyl groups may be bonded to a combination of the 1st, 1', and 3rd positions of the indene ring, or a combination of the 1st and 1' positions of the indene ring.

[0031] In formula (1), the methylene group of the vinylbenzyl group may be at any of o, m, and p positions, but preferably at m or p positions. In formula (1), when one molecule contains two or three vinylbenzyl groups, the two or three vinylbenzyl groups may be any of o, m, and p forms, or may be a combination of these, but preferably includes p forms, may be only p forms, or may be a combination of m and p forms. In the case where the resin composition contains two or more types of monomers represented by formula (1), the positions of the methylene groups of the vinylbenzyl groups between the two or more monomers may be the same or different from each other. In the case where the resin composition contains two or more types of monomers represented by formula (1), the vinylbenzyl groups in the mixture of the two or more monomers may be one or a combination of two or more of o, m, and p forms, preferably includes p forms, may be only p forms, or may be a combination of m and p forms. In this case, the mass ratio of m-form to p-form in the resin composition or its cured product is preferably 40:60 to 60:40.

[0032] The following describes a method for synthesizing a monomer of the vinylbenzyl compound. The vinylbenzyl compound is a compound that is specified by its molecular structure, regardless of the synthesis method described below.

[0033] As a method for synthesizing a monomer of a vinylbenzyl compound, for example, a method of reacting a base compound having a desired structure such as indene or fluorene with a styrene having a halogenated methyl group in the presence of a basic compound can be mentioned. As a styrene having a halogenated methyl group, for example, o-chloromethylstyrene, m-chloromethylstyrene, p-chloromethylstyrene, etc. can be mentioned, and these can be one or a mixture of two or more. As a basic compound, an alkali metal hydroxide, an alkali metal alkoxide, etc. can be mentioned.

[0034] A phase transfer catalyst may be used in the above reaction. Examples of the phase transfer catalyst include tetra-n-butylammonium bromide. The reaction may be carried out by solution polymerization. The reaction may be carried out, for example, under heating and stirring. A polymerization inhibitor may be added to the reaction system. Examples of the polymerization inhibitor include phenothiazine. The obtained product may be purified by a known method such as concentration, reprecipitation, washing, etc., as necessary.

[0035] The obtained monomer may be a single compound or a monomer mixture of two or more compounds. For example, when indene is used as the base compound, a compound in which a vinylbenzyl group is directly bonded to at least one carbon atom at the 1st, 2nd, and 3rd positions of an indene ring is synthesized, but two or more isomeric vinylbenzyl compounds having different bonding sites may be included in the monomer mixture. In addition, depending on the synthesis conditions, a compound in which a vinylbenzyl group is directly bonded to at least two carbon atoms at the 1st, 2nd, and 3rd positions of an indene ring can be obtained. In this case, two or more vinylbenzyl compounds having different numbers of bonds and bonding sites of vinylbenzyl groups to an indene ring may be included in the monomer mixture.

[0036] When the vinylbenzyl compound is a monomer, the molecular weight is not particularly limited, but from the viewpoints of moldability and handling, it is preferably from 200 to 800, more preferably from 250 to 750, and even more preferably from 300 to 700. When the vinylbenzyl compound is a monomer, the molecular weight is the weight average molecular weight (Mw) in the case of a mixture of a plurality of compounds.

[0037] Among the vinylbenzyl compounds, the prepolymer will be described below. The vinylbenzyl compound as the prepolymer is preferably a hydrocarbon compound, and among the hydrocarbon compounds, it is preferably a compound having an indene ring, an indane ring, a phenanthrene ring, an acenaphthylene ring, a fluorene ring, etc., or a combination thereof, more preferably a compound having an indene ring, a fluorene ring, or a combination thereof, and even more preferably a compound having an indene ring.For example, the vinylbenzyl compound may be a prepolymer having one or more vinylbenzyl groups and a structural unit having one indene ring.

[0038] The prepolymer can be obtained by polymerizing a monomer. The vinylbenzyl group may be introduced from the monomer. For example, a monomer having one or more vinylbenzyl groups may be used, and a monomer having two or more vinylbenzyl groups is preferably used. The polymerization may not be completed completely, but may be stopped when a certain amount of vinylbenzyl groups derived from the monomer remain. For example, in order to obtain a curable prepolymer in a liquid state, the polymerization may be stopped when the viscosity of the polymerization reaction system of the curable prepolymer reaches a certain level. In the polymerization of the prepolymer, an oligomer may be used together with or instead of the monomer. For example, the monomer of the vinylbenzyl compound described above may be used in the polymerization of the prepolymer, and an oligomer of this monomer may be used.

[0039] When the vinylbenzyl compound is a prepolymer, the weight average molecular weight (Mw) may be, for example, 5,000 to 50,000, or 10,000 to 30,000, from the viewpoint of the fluidity of the resin composition.

[0040] Next, a method for obtaining a vinylbenzyl compound as a prepolymer by polymerizing a vinylbenzyl compound will be described. The polymerization of the vinylbenzyl compound is preferably carried out by radical polymerization so that no polar component is generated in the reaction product. The radical polymerization can be carried out using a radical polymerization initiator. The polymerization can be carried out by solution polymerization, and the polymerization solvent is not particularly limited. For example, one or a combination of two or more organic solvents used in the resin composition described later may be used as the polymerization solvent.

[0041] The radical polymerization initiator may be a thermal radical polymerization initiator or a photoradical polymerization initiator, but is preferably a thermal radical polymerization initiator. The radical polymerization initiator is not particularly limited, and examples thereof include azo-based polymerization initiators and organic peroxide-based polymerization initiators. Specifically, for example, the initiator may be appropriately selected from azo-based polymerization initiators and organic peroxide-based polymerization initiators exemplified as curing accelerators described later. The radical polymerization initiator may be used alone or in combination of two or more.

[0042] The vinylbenzyl compound as the prepolymer may be a homopolymer or a copolymer of the vinylbenzyl compound. The copolymer may be a copolymer of two or more vinylbenzyl compounds, or a copolymer of the vinylbenzyl compound and another monomer. In the case of a copolymer, it may be a random copolymer, a block copolymer, or the like.

[0043] The oligomer of the vinylbenzyl compound may be a polymer having a low degree of polymerization of the above-mentioned monomer.

[0044] The vinylbenzyl compounds may be used alone or in combination of two or more.

[0045] From the viewpoint of heat resistance, the vinylbenzyl compound may be 10% by mass or more, 20% by mass or more, or 30% by mass or more, based on the solid content of the resin composition. On the other hand, from the viewpoint of adhesion, the vinylbenzyl compound may be 70% by mass or less, 60% by mass or less, or 50% by mass or less, based on the solid content of the resin composition. The vinylbenzyl compound may be, for example, 10 to 70% by mass, 20 to 60% by mass, or 30 to 50% by mass, based on the solid content of the resin composition.

[0046] In the present disclosure, the "solid content" of a resin composition refers to components in the resin composition other than volatile substances such as water, the solvent described below, etc. The solid content is a component that remains without volatilization when the resin composition is dried, and includes those that are liquid at room temperature around 25°C, and does not necessarily mean that they are solid.

[0047] The vinylbenzyl compound may be, for example, 50% by mass or more, 60% by mass or more, or 70% by mass or more with respect to the total amount of the vinylbenzyl compound and the phosphorus-based compound having a melting point of 230° C. or more, which will be described later. On the other hand, the vinylbenzyl compound may be, for example, 95% by mass or less, 90% by mass or less, or 85% by mass or less with respect to the total amount of the vinylbenzyl compound and the phosphorus-based compound having a melting point of 230° C. or more in the resin composition. The vinylbenzyl compound may be, for example, 50 to 95% by mass, 60 to 90% by mass, or 70 to 85% by mass with respect to the total amount of the vinylbenzyl compound and the phosphorus-based compound having a melting point of 230° C. or more in the resin composition.

[0048] <Phosphorus compounds with a melting point of 230°C or higher> The phosphorus-based compound having a melting point of 230° C. or higher (hereinafter, sometimes referred to as "phosphorus-based compound A") is not particularly limited as long as it is a phosphorus-based compound having a melting point of 230° C. or higher, and the phosphorus-based compound A is preferably an organic phosphorus-based compound. The phosphorus-based compound A may be a flame retardant.

[0049] From the viewpoint of heat resistance, the melting point of the phosphorus-based compound A is preferably 230° C. or higher. When a phosphorus-based compound having a high melting point of 230° C. or higher is used, the glass transition point (Tg) of the cured product of the resin composition tends to be high. Although not being bound by a specific theory, it is considered that the reason for this is that when the phosphorus-based compound has a high melting point, the temperature at which the resin composition containing the phosphorus-based compound becomes apparently soft due to the melting of the phosphorus-based compound becomes high.

[0050] The melting point of the phosphorus-based compound A is more preferably 240° C. or higher, further preferably 250° C. or higher, further preferably 280° C. or higher, and further preferably 300° C. or higher. On the other hand, the melting point of the phosphorus-based compound A may be, for example, 500° C. or lower, or 400° C. or lower. The melting point of the phosphorus-based compound A may be, for example, 230 to 500°C, 240 to 500°C, 250 to 500°C, 280 to 400°C, or 300 to 400°C.

[0051] The phosphorus-based compound A is not particularly limited in structure, but examples thereof include phosphorus-based compounds such as compounds having a phosphine oxide group, organic cyclic phosphorus compounds, and phosphazene compounds, and has a melting point of 230° C. or higher.

[0052] An example of a compound having a phosphine oxide group is a compound represented by the following formula (2). A 1 -LA 2 (2)

[0053] In formula (2), A 1 and A 2 each independently represents a diarylphosphine oxide group, and L is a divalent linking group.

[0054] In formula (2), A 1 and A 2 each independently represents a diarylphosphine oxide group. 1 and A 2may be, for example, each independently a diphenylphosphine oxide group. The two phenyl groups of the diphenylphosphine oxide group may be each independently substituted or unsubstituted, but are preferably unsubstituted. 1 and A 2 may each independently be a diphenylphosphine oxide group represented by -P(=O)(C6H5)2.

[0055] In formula (2), L is a divalent linking group. It is preferable that L does not contain an oxygen atom. L may be, for example, a divalent hydrocarbon group.

[0056] L may be, for example, one divalent linking group selected from the group consisting of an alkylene group and an arylene group, or a divalent linking group formed by combining two or more groups selected from the group consisting of an alkylene group and an arylene group. In L, the alkylene group may, for example, be an alkylene group having 1 to 8, 1 to 5, or 1 to 3 carbon atoms. In L, the arylene group may, for example, be a phenylene group.

[0057] L is, for example, -L 1 -L 2 -L 3 L may be a divalent linking group represented by the formula: 1 and L 3 Each of L independently represents an alkylene group, and may be, for example, an alkylene group having 1 to 3 carbon atoms. 2 represents an arylene group, which may be, for example, a substituted or unsubstituted phenylene group. 2 may preferably be an unsubstituted phenylene group.

[0058] An example of the compound represented by formula (2) having a melting point of 230° C. or higher is xylylenebisdiphenylphosphine oxide (eg, p-xylylenebisdiphenylphosphine oxide, etc.).

[0059] Examples of the phosphorus-based compound A include 10-(2,5-dihydroxyphenyl)-10h-9-oxa-10-phospha-phenanthrene-10-oxide, spirocyclophosphazene, and (4-vinylbenzyl)diphenylphosphine oxide.

[0060] The phosphorus-based compound A may be used alone or in combination of two or more kinds.

[0061] From the viewpoint of flame retardancy, the phosphorus-based compound A may be 1 mass% or more, 2 mass% or more, or 5 mass% or more with respect to the solid content of the resin composition. On the other hand, from the viewpoint of dielectric loss tangent, the phosphorus-based compound A may be 30 mass% or less, 20 mass% or less, or 10 mass% or less with respect to the solid content of the resin composition. The phosphorus-based compound A may be, for example, 1 to 30 mass%, 2 to 20 mass%, or 5 to 10 mass% with respect to the solid content of the resin composition.

[0062] The phosphorus-based compound A may be, for example, 50% by mass or less, 40% by mass or less, or 30% by mass or less, based on the total amount of the vinylbenzyl compound and the phosphorus-based compound A. On the other hand, the phosphorus-based compound A may be, for example, 5% by mass or more, 10% by mass or more, or 15% by mass or more, based on the total amount of the vinylbenzyl compound and the phosphorus-based compound A. The phosphorus-based compound A may be, for example, 5 to 50% by mass, 10 to 40% by mass, or 15 to 30% by mass, based on the total amount of the vinylbenzyl compound and the phosphorus-based compound A in the resin composition.

[0063] <Other ingredients> The resin composition may contain other components in addition to the vinylbenzyl compound and the phosphorus-based compound A, as necessary. Examples of other components include fillers, elastomers, curing accelerators, solvents, antioxidants, heat stabilizers, antistatic agents, UV absorbers, pigments, colorants, and lubricants.

[0064] The filler may be an inorganic filler, an organic filler, or a combination thereof. When the resin composition contains a filler, the amount of the filler may be, for example, 30 to 85 mass %, 40 to 80 mass %, or 50 to 75 mass % relative to the solid content of the resin composition.

[0065] Examples of inorganic fillers include silica (SiO2), alumina (Al2O3), titanium oxide, barium titanate, strontium titanate, potassium titanate, calcium titanate, aluminum carbonate, magnesium hydroxide, aluminum hydroxide, aluminum silicate, calcium carbonate, calcium silicate, magnesium silicate, silicon nitride, boron nitride, aluminum borate, silicon carbide, mica, beryllia, clay, talc, etc. From the viewpoint of dielectric properties, silica is preferred.

[0066] The shape and size of the inorganic filler are not particularly limited. The average particle size of the filler may be, for example, 0.01 to 20 μm, or 0.1 to 10 μm. Here, the average particle size of the filler is the particle size at a point corresponding to an integrated value of 50% in the volume-based particle distribution by the laser diffraction scattering method.

[0067] The inorganic fillers may be used alone or in combination of two or more. When the resin composition contains an inorganic filler, the inorganic filler may be present in an amount of, for example, 20 to 80 mass %, 20 to 70 mass %, or 30 to 60 mass % relative to the solid content of the resin composition.

[0068] An example of the organic filler is a silicone condensate having an alkoxy group and a phenyl group (hereinafter, sometimes referred to as "silicone condensate S").

[0069] In the silicone condensate S, the alkoxy group may be, for example, an alkoxy group having 1 to 3 carbon atoms, and specific examples thereof include a methoxy group, an ethoxy group, a propoxy group, etc. In the silicone condensate S, the phenyl group may be substituted or unsubstituted, but an unsubstituted phenyl group is preferred. The silicone condensate S is preferably a solid at 70°C.

[0070] It is preferable that 20% or more of the siloxane units in the silicone condensate S are siloxane units having a phenyl group and an alkoxy group (such as a methoxy group, an ethoxy group, or a propoxy group), and it is even more preferable that the content of siloxane units having a phenyl group and an alkoxy group (also referred to as the phenylalkoxysilane content) is 40% or more. The silicone condensate S preferably contains, as siloxane units, a siloxane unit having one phenyl group and three alkoxy groups, and a siloxane unit having four alkoxy groups, and it is particularly preferable that the siloxane units are composed of a siloxane unit having one phenyl group and three alkoxy groups, and a siloxane unit having four alkoxy groups.

[0071] The silicone condensate S can be obtained, for example, by dehydration condensation of one or more silanes. One example of the silicone condensate S can be produced by dehydration condensation using a silane having one phenyl group and three alkoxy groups and a silane having four alkoxy groups. An example of the silane having one phenyl group and three alkoxy groups is phenyltriethoxysilane. An example of the silane having four alkoxy groups is tetraethoxysilane.

[0072] The condensation reaction rate of the silicone condensate S in the dehydration condensation is preferably 90% or more. The condensation reaction rate of the silicone condensate S is calculated by the following formula. Condensation reaction rate = [Amount of dehydration (g)] / [18 × (total number of moles of alkoxy groups) / 2] × 100 (%) The dehydration reaction can be carried out by heating in the presence of an acid catalyst. In the above formula, [18 x (moles of all alkoxy groups) / 2] is 1 / 2, since theoretically, one molecule of water is produced from two alkoxy groups, and this is multiplied by the molecular weight of water (18).

[0073] The silicone condensate S may be used alone or in combination of two or more kinds. When the resin composition contains the silicone condensate S, from the viewpoint of further improving the heat resistance and the flame retardancy, the silicone condensate S may be, for example, 1% by mass or more, 5% by mass or more, or 10% by mass or more, based on the solid content of the resin composition. From the viewpoint of the dielectric loss tangent, the silicone condensate S may be, for example, 40% by mass or less, 30% by mass or less, or 20% by mass or less, based on the solid content of the resin composition. When the resin composition contains the silicone condensate S, the silicone condensate S may be, for example, 1 to 40% by mass, 5 to 30% by mass, or 10 to 20% by mass, based on the solid content of the resin composition. The organic fillers may be used alone or in combination of two or more. When the resin composition contains an organic filler, the amount of the organic filler may be, for example, 1 to 40 mass %, 5 to 30 mass %, or 10 to 20 mass % relative to the solid content of the resin composition.

[0074] Examples of the elastomer include styrene-based elastomers, olefin-based elastomers, urethane-based elastomers, polyester-based elastomers, polyamide-based elastomers, acrylic-based elastomers, and silicone-based elastomers. The elastomers may be used alone or in combination of two or more.

[0075] As the curing accelerator, for example, a radical polymerization initiator can be used. The radical polymerization initiator may be a thermal radical polymerization initiator or a photoradical polymerization initiator, but a thermal radical polymerization initiator is preferred. The radical polymerization initiator is not particularly limited, and examples thereof include an azo-based polymerization initiator and an organic peroxide-based polymerization initiator. Examples of the azo polymerization initiator include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylpropanenitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylpropionate)dimethyl, 1,1'-azobis(methyl cyclohexylcarboxylate), 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), 4,4'-azobis(3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl 4-cyanopentanoate), and 1,1'-azobis(cyclohexane-1-carbonitrile). Examples of the organic peroxide polymerization initiator include dicumyl peroxide, dibenzoyl peroxide, 2-butanone peroxide, tert-butyl perbenzoate, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, bis(tert-butylperoxyisopropyl)benzene, and tert-butyl hydroperoxide.

[0076] The curing accelerators may be used alone or in combination of two or more. The amount of the curing accelerator may be, for example, 0.01 to 3 mass %, 0.05 to 2 mass %, or 0.1 to 1 mass % relative to the solid content of the resin composition.

[0077] The resin composition may be a solvent-free resin composition or may contain a solvent. The solvent can adjust the viscosity of the resin composition to further improve the coatability. The solvent is preferably an organic solvent.

[0078] Examples of organic solvents include alcohol-based solvents such as ethanol, propanol, butanol, methyl cellosolve, ethylene glycol monobutyl ether, and propylene glycol monomethyl ether; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ether-based solvents such as tetrahydrofuran; aromatic hydrocarbon-based solvents such as toluene, xylene, and mesitylene; nitrogen-containing solvents such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone; sulfur-containing solvents such as dimethylsulfoxide; and ester-based solvents such as γ-butyrolactone. The organic solvents may be used alone or in combination of two or more.

[0079] When the resin composition contains a solvent, the solid content (solid content concentration) of the resin composition is, for example, preferably 30 to 90 mass %, more preferably 40 to 80 mass %, and even more preferably 50 to 65 mass %, based on the total mass of the resin composition. When the solid content concentration of the resin composition is within the above range, the resin composition is easy to handle, and the impregnation into the substrate and the appearance of the produced prepreg are good.

[0080] <Method of producing resin composition> The method for producing the resin composition is not particularly limited. The resin composition according to one embodiment is not limited by the production method, and its features are as described in the present disclosure. As an example of the method for producing the resin composition, a vinylbenzyl compound, a phosphorus-based compound A, and an optional component are added and mixed as necessary to obtain a resin composition. More specifically, for example, a vinylbenzyl compound, a phosphorus-based compound A, etc. are dissolved or dispersed in a solvent, and other components are added and mixed as necessary to obtain a resin composition. The conditions such as the mixing order, temperature, and time of each component are not particularly limited, and may be appropriately adjusted according to the type of raw material, production scale, production equipment, etc.

[0081] [Prepreg] According to one embodiment, a prepreg containing a resin composition or a semi-cured product of the resin composition can be provided. This prepreg can be formed, for example, by using a resin composition and a fiber substrate. The resin composition can be any of the above-mentioned resin compositions. Details of the resin composition are as described above.

[0082] The prepreg may contain the above-mentioned resin composition or a semi-cured product of the above-mentioned resin composition. In the present disclosure, one index of a semi-cured product may be the B-stage state according to JIS K 6800 (1985). The prepreg may contain, for example, a resin composition or a semi-cured product of the resin composition and a fiber substrate such as a sheet-shaped fiber substrate. In the prepreg, the resin composition may be in an uncured state, but the resin composition may be in a partially or entirely semi-cured state. For example, the prepreg can be cured by heat treatment or the like to obtain a cured product.

[0083] The prepreg can be obtained, for example, by coating a fiber substrate with a resin composition and drying it. For example, the prepreg can be obtained by impregnating and coating a fiber substrate with a resin composition and drying the fiber substrate impregnated with the resin composition. The drying is preferably performed at a temperature at which volatile components such as a solvent that may be contained in the resin composition are removed or higher, and may be performed at a temperature at which the thermosetting resin contained in the resin composition is semi-cured or higher depending on the application. In addition, the drying is preferably adjusted so that the thermosetting resin contained in the resin composition is not completely cured. From this viewpoint, the drying temperature may be, for example, 80 to 200 ° C., and the drying time may be, for example, 1 to 30 minutes depending on the drying temperature, the drying device, its scale, and the like.

[0084] The fibrous substrate may be any of woven, knitted, and nonwoven fabrics. The fibrous substrate may be provided in the form of chopped strand mat, roving, and the like. The material of the fibers may be either inorganic or organic. Examples of inorganic fibers include glass fibers and carbon fibers. Examples of glass fibers include E glass, D glass, S glass, and Q glass. Examples of organic fibers include polyimide, polyester, and tetrafluoroethylene. The fiber substrate may be one of these fibers alone or two or more of these fibers in combination. From the viewpoints of dielectric properties and heat resistance, the material of the fiber substrate is preferably inorganic fiber, and more preferably glass fiber.

[0085] The fiber base material may be appropriately selected depending on the application of the prepreg, but a sheet-like fiber base material is preferred. The sheet-like fiber base material may be, for example, any of various sheet-like fiber base materials used in known laminates for electrical insulating materials. The thickness of the sheet-like fiber substrate is not particularly limited, but is preferably 0.02 to 0.5 mm, for example. The thickness is measured at five points at equal distances over the entire surface of the sheet-like fiber substrate, and the arithmetic average value of the five points is taken as the thickness.

[0086] [Resin film] According to one embodiment, a resin film including a resin composition or a semi-cured product of the resin composition can be provided. The resin film can be produced using the resin composition. Details of the resin composition are as described above.

[0087] The resin film may contain the above-mentioned resin composition or a semi-cured product of the above-mentioned resin composition. In the resin film, the resin composition may be in an uncured state, but the resin composition may be in a partially or entirely semi-cured state. For example, the resin film can be cured by heat treatment or the like to obtain a cured product. The resin film can be obtained, for example, by applying a resin composition to a substrate and drying it. The drying can be performed, for example, in the same manner as in the above-mentioned method for producing a prepreg. After drying the resin film on the substrate, a product may be provided as a combination of the resin film and the substrate. For example, in this method, a resin film can be provided to form an insulating layer or the like on the substrate in electronic devices or the like. In another method, after drying the resin film on the substrate, the resin film may be peeled off from the substrate to provide the resin film as a product.

[0088] The substrate may be either an inorganic substrate or an organic substrate, and examples of the substrate include a glass substrate, a metal substrate such as a metal foil or a metal plate, a plastic substrate such as a plastic plate or a plastic film, a paper substrate, or a fiber substrate as described above for the prepreg. In order to peel the resin film from the substrate, a substrate having a release layer formed on the surface may be used.

[0089] [Metal-clad laminate] According to one embodiment, a metal-clad laminate including a cured resin composition and a metal foil can be provided. The metal-clad laminate may be, for example, a metal-clad laminate including a cured prepreg and a metal foil. According to another embodiment, a metal-clad laminate formed by using a prepreg and a metal foil can be provided. The metal-clad laminate may be, for example, a metal-clad laminate including a cured prepreg and a metal foil. The details of the resin composition and the prepreg are as described above.

[0090] The metal-clad laminate preferably includes a resin cured product layer containing a resin cured product and a metal foil disposed on at least one surface of the resin cured product layer. The resin cured product layer includes a cured product of the resin composition described above, but may be the cured product of the prepreg described above. For example, in the metal-clad laminate, a metal foil is disposed on at least one surface of the cured product of the prepreg, and more preferably, a metal foil is disposed on both surfaces of the cured product of the prepreg. The metal-clad laminate may be manufactured by disposing a metal foil on at least one surface of a single sheet-like prepreg, or may be manufactured by laminating two or more sheet-like prepregs and disposing a metal foil on at least one surface of the outermost surface of the laminate. For example, the metal-clad laminate may be manufactured by laminating two or more sheet-like prepregs and disposing a metal foil on both surfaces of the laminate.

[0091] Hereinafter, a method of arranging a metal foil on a laminate of two or more sheet-like prepregs will be described as a specific example of a method for producing a metal-clad laminate.

[0092] First, two or more sheet-like prepregs are laminated to obtain a laminate. In this laminate, the two or more sheet-like prepregs may be the same as each other, or may be partially or entirely different. In the laminate, at least one of the two or more sheet-like prepregs may be obtained using the resin composition according to one embodiment.

[0093] Next, a metal foil is placed on at least one surface of this laminate. The laminate with the metal foil disposed thereon is heated and pressurized. This advances the curing reaction of the sheet-like prepreg, and a cured prepreg can be obtained. Also, adjacent sheet-like prepregs can be fixed to each other. The heating and pressurizing conditions are not particularly limited, but may be, for example, a temperature of 100 to 300°C, a time of 10 to 300 minutes, and a pressure of 1.5 to 5 MPa. After heating and pressurizing, reheating may be performed to further advance the curing of the prepreg. In this case, the reheating temperature may be 100 to 300°C. As a method for applying pressure, for example, an autoclave molding machine, a multi-stage press machine, a multi-stage vacuum press machine, a continuous molding machine, etc. can be used.

[0094] The metal of the metal foil is not particularly limited, and examples thereof include copper, nickel, aluminum, gold, silver, platinum, molybdenum, ruthenium, tungsten, iron, titanium, chromium, and alloys containing two or more of these metal elements. Industrially, it is preferable to use single metals such as copper, nickel, and aluminum. By using copper as the metal foil, a copper-clad laminate can be provided.

[0095] [Printed wiring board] According to one embodiment, a printed wiring board including a cured product of the resin composition can be provided. Details of the resin composition are as described above.

[0096] In the printed wiring board, the cured product of the resin composition can be produced using a resin composition, a prepreg, a resin film, a metal-clad laminate, or a combination thereof. For example, a printed wiring board can be provided by forming wiring on a cured product of a prepreg by a known method. In another example, a printed wiring board can be provided by forming wiring using a metal-clad laminate by a known method. A printed wiring board that combines these examples may be used. Details of the prepreg, the resin film, and the metal-clad laminate are as described above.

[0097] The printed wiring board may be either a single-layer printed wiring board or a multi-layer printed wiring board.

[0098] [Semiconductor package] According to one embodiment, a semiconductor package including a printed wiring board and a semiconductor element can be provided. More specifically, a semiconductor package including a printed wiring board including a cured product of a resin composition and a semiconductor element can be provided. Details of the resin composition are as described above. Details of the cured product of the resin composition and the printed wiring board are also as described above. The semiconductor package can be manufactured, for example, by mounting a semiconductor element, a memory, or the like on a printed wiring board by a known method. The cured product of the resin composition may be used as an insulating material, a sealing material, or the like of the semiconductor package. EXAMPLES

[0099] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0100] [Method of measuring weight average molecular weight (Mw)] The weight average molecular weight was calculated from a calibration curve using standard polystyrene by gel permeation chromatography (GPC). The calibration curve was approximated by a third order equation using standard polystyrene: TSKstandard POLYSTYRENE (Type: A-2500, A-5000, F-20, F-80) (manufactured by Tosoh Corporation, trade name). The measurement conditions for GPC are shown below.

[0101] Equipment: High-speed GPC equipment HLC-8320GPC (Tosoh Corporation, product name) Detector: Ultraviolet absorption detector UV-8320 (Tosoh Corporation, product name) Columns: Guard column; TSKgel guardcolumn Super(HZ)-M+, column; TSKgel SuperMultipore HZ-M (2 columns), reference column; TSKgel SuperH-RC (2 columns) (all products of Tosoh Corporation) Column size: 4.6 x 20 mm (guard column), 4.6 x 150 mm (column), 6.0 x 150 mm (reference column) Eluent: Tetrahydrofuran Sample concentration: 10mg / 1mL Injection volume: 20μL or 2μL Flow rate: 0.35mL / min Measurement temperature: 40℃

[0102] [Production of vinylbenzyl compounds] A 500 mL reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet was charged with 35.6 parts by mass of indene, 101.2 parts by mass of the following chloromethylstyrene, 7.1 parts by mass of tetra-n-butylammonium bromide (manufactured by Kanto Chemical Co., Ltd.) as a phase transfer catalyst, 0.1 parts by mass of phenothiazine as a polymerization inhibitor, and 77.6 parts by mass of toluene as a solvent, and the mixture was heated and stirred at 40° C. while blowing in nitrogen at a flow rate of 50 mL / min.

[0103] Chloromethylstyrene "CMS-P": AGC Seimi Chemical Co., Ltd., a mixture of m- and p-forms, with m-form content of 50% by mass and p-form content of 50% by mass.

[0104] Next, 46.5 parts by mass of the following aqueous sodium hydroxide solution was added dropwise over 20 minutes, and the mixture was stirred at 60° C. for another 9 hours. Nitrogen was continuously blown in during the reaction. The mixture was cooled to room temperature (25° C.) and neutralized with a 10% aqueous hydrochloric acid solution, then washed twice with pure water, and the toluene was distilled off under reduced pressure. The resulting viscous liquid was washed with methanol and then vacuum dried to obtain a vinylbenzyl compound.

[0105] Aqueous solution of sodium hydroxide: an aqueous solution of sodium hydroxide with a concentration of 48% by mass, Kanto Chemical Co., Ltd.

[0106] The resulting vinylbenzyl compound is 1 H-NMR analysis confirmed that the compound had a structure in which the two hydrogen atoms directly bonded to the carbon atom at position 1 of indene represented by the following formula (3) were substantially all substituted with vinylbenzyl groups. GPC analysis also confirmed that the obtained vinylbenzyl compound was a mixture of one having two vinylbenzyl groups and one having three vinylbenzyl groups. The weight-average molecular weight (Mw) of the vinylbenzyl compound was 500.

[0107] [ka]

[0108] [Production of silicone condensation products] Into a four-necked separable flask equipped with a thermometer, a cooling tube, a Dean-Stark tube, and a stirrer, 50.0 g of phenyltriethoxysilane (manufactured by Kanto Chemical Co., Ltd.), 4.8 g of tetraethoxysilane (manufactured by Kanto Chemical Co., Ltd.), 2.36 g of hydrochloric acid (manufactured by Kanto Chemical Co., Ltd.) with a concentration of 0.1 mol / L, 550 g of ethanol (manufactured by Kanto Chemical Co., Ltd.), and 900 g of distilled water were added and stirred at 20°C for 2 hours. Thereafter, a dehydration condensation reaction was carried out until the condensation reaction rate reached 95%, and 28.5 g of a silicone condensate with a phenylalkoxysilane content of 94% was produced. The obtained silicone condensate was a solid powder at 70°C.

[0109] [Production of resin composition] Each component shown in Table 1 was stirred and mixed at 25°C with toluene in the amounts shown in Table 1 to prepare resin compositions of Examples 1 and 2 and Comparative Example 1 having a solid content concentration of about 60% by mass. In Table 1, the unit of the amount of each component is parts by mass, and when the component is a solution, it means parts by mass converted into solid content.

[0110] Details of each material listed in Table 1 are as follows.

[0111] Vinylbenzyl compounds: Prepared as above

[0112] Inorganic filler: Silica (average particle size: 2.3 μm)

[0113] Silicone condensate: Produced as above

[0114] Phosphorus compound 1: A compound represented by the following formula (p-xylylenebisdiphenylphosphine oxide) (melting point 330°C) [ka]

[0115] Phosphorus compound 2: Compound represented by the following formula (melting point 184°C) [ka]

[0116] Curing accelerator: organic peroxide polymerization initiator (bis(tert-butylperoxyisopropyl)benzene, NOF Corporation "Perbutyl-P" (product name))

[0117] [Preparation of prepreg] The resin composition obtained as described above was applied to a glass cloth having a thickness of 0.03 mm by impregnation, and the cloth was dried by heating to semi-cure, thereby obtaining a prepreg. The drying temperature and drying time may be appropriately determined depending on the amount of organic solvent used and the boiling point of the organic solvent used, but drying was performed for about 10 minutes at 120° C. The amount of the resin composition used was such that the solid content concentration derived from the thermosetting resin composition in the prepreg after drying was 82 mass %.

[0118] [Preparation of double-sided copper-clad laminate] An 18 μm-thick electrolytic copper foil was laminated on both sides of the prepreg obtained as described above, with the matte side facing the prepreg, and heated and pressed at 230° C. for 120 minutes under vacuum press conditions of 2 MPa to produce a double-sided copper-clad laminate.

[0119] [Evaluation and measurement methods]

[0120] <Glass transition temperature (Tg)> The double-sided copper-clad laminate obtained above was immersed in a 10% by mass solution of ammonium persulfate (manufactured by Mitsubishi Gas Chemical Co., Ltd.), which is a copper etching solution, to remove the copper foil, and a test piece of 30 mm in length and 5 mm in width was cut from the board from which the copper foil had been removed. The glass transition temperature (Tg) was determined from the peak of tan δ obtained by dynamic mechanical analysis (DMA) under conditions of a temperature rise of 5°C / min in tension mode. This glass transition temperature (Tg) was used as an index of heat resistance. The measuring device used was Rheogel-E4000 manufactured by UBM Co., Ltd. The results (Tg) are shown in Table 1.

[0121] <Flame retardancy> The double-sided copper-clad laminate obtained above was immersed in a 10 mass% solution of ammonium persulfate (manufactured by Mitsubishi Gas Chemical Company, Inc.), which is a copper etching solution, to remove the copper foil, and a 13 mm x 125 mm evaluation board was cut out from the board from which the copper foil had been removed. In accordance with the vertical burning test (UL94-V), the upper end of this evaluation board was held, and the flame of a gas burner was applied vertically to the lower end of the evaluation board for 10 seconds, and then the flame of the gas burner was removed. If the flame went out after the flame of the gas burner was removed, the flame of the gas burner was immediately applied for another 10 seconds, and the flame was then removed. The average burning time after the flame was removed was calculated. The vertical burning test was evaluated with N=5 for each test number.

[0122] [Table 1]

[0123] As shown in Table 2, it is understood that Examples 1 and 2 have a higher glass transition temperature (Tg (°C)) and are excellent in heat resistance compared to Comparative Example 1. In addition, Examples 1 and 2 have a shorter average combustion time compared to the average combustion time of Comparative Example 1, indicating that they have good flame retardancy.

Claims

1. A resin composition comprising a compound having a vinylbenzyl group and a phosphorus-based compound having a melting point of 230° C. or higher.

2. The resin composition according to claim 1 , further comprising an inorganic filler.

3. The resin composition according to claim 1, further comprising a silicone condensate having an alkoxy group and a phenyl group.

4. A prepreg comprising the resin composition according to any one of claims 1 to 3 or a semi-cured product of the resin composition.

5. A resin film comprising the resin composition according to any one of claims 1 to 3 or a semi-cured product of the resin composition.

6. A metal-clad laminate comprising a cured product of the resin composition according to any one of claims 1 to 3 and a metal foil.

7. A printed wiring board comprising a cured product of the resin composition according to any one of claims 1 to 3.

8. A semiconductor package comprising the printed wiring board according to claim 7 and a semiconductor element.

Citation Information

Patent Citations

  • Thermosetting resin composition and electronic part using the same

    JP2007119531A

Cited By

  • Resin composition, prepreg, resin-equippped film, resin-equipped metal foil, metal-clad laminated plate, and wiring board

    WO2025258487A1